The Conversational Discourse Elements related to Donation: A Conversation Analysis Approach - Surin, Phongsatorn; Chotidilok, Suntaree; Satham, Sakaoduen (Journal of Arts and Thai Studies, 2024)
Objectives: This article aims to analyze the conversational discourse elements related to donation. Methods: This research is language research. Qualitative research methods were used. It uses Conversational Analysis of Sacks, Schegloff, and Jefferson’s (1974) serves as a framework for analyzing the conversational discourse about "donation" which are produced and published by youtube channel Pimrypie of 82 videos. Results: The conversational discourse elements related to donation. It was revealed that there were 8 components of conversational discourse elements related to donation: interruption, overlapping, other repetition, terminate, repair, silence, feedback, and backchannel. It was able to explain that which interlocutor tends to influence or control the behavior of others when interacting. Application of this study: The study of conversational discourse elements provided the understanding of power relations, power negotiation, and the role language in meaning construction of donation. Additionally, it was able to be way to the further study of Critical Discourse Analysis (CDA).